Enhancing knowledge sharing capabilities through online communication in Malaysia higher learning institutions/ Ap-Azli Bunawan ... [et al.] - Yaacob, Raja Abdullah; Mat Isa, Azman; Bunawan, Ap-Azli (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Progress in knowledge sharing has offered today's information seekers' different opportunities to access the information resources in variety of formats, including commonly-available electronic information resources, such as CD-ROMs, databases, Web-OPACs, and the Internet. In some instances, these resources are replacing the print-based information resources as the primary media for the storage and communication of recorded information. This research attempts to explore the usage of electronic recourses and knowledge sharing practices in Malaysian Higher Learning Institutions as well as to propose a new approach in using e-literature system. Knowledge sharing may not be seen as essential key to the success of an organization, but contrary they are significant when a failure or mismanagement occurs. Malaysian Higher Learning Institutions is bound to stringent regulations, particularly at international level. Therefore, in order to enhance the international map, it is vital for Higher Learning Institutions in Malaysia to be certain about their information and knowledge and research resources available. Knowledge sharing capabilities through online communication is a highly complex task involving the interaction among users, their information needs, and the information resources. The heterogeneous environment in which users confront in academic libraries today has increased the complexity of, not only the format of information, but also the number of resources has grown exponentially. In the traditional library, people dealt with fairly limited spectrum from the range of information sources - some basic reference sources, books, magazines, a few major newspapers, and scholarly journals. The current digital environment has expanded these resources from people encounter in their research process, requiring them to navigate back and forth from the print to the electronic environment. An electronic literature (e-literature) system could play a crucial role in ensuring the continuous process in the sharing of knowledge.